Efficiency of Sharia Life Insurance in Indonesia and Malaysia: The Effect of Profitability and Firm Size - Riska Aprilia; A. Jajang W. Mahri; Aneu Cakhyaneu (Indonesian Journal of Economics and Management, 2022)
The performance of sharia life insurance in Indonesia and Malaysia has increased and decreased, the declining performance of sharia life insurance causes low income, indicating inefficiency. Inefficiency has adverse effects that will hinder the firm's growth. The purpose of this study is to measure the technical efficiency value of 24 sharia life insurance companies and analyze the effect of profitability level and firm size on the level of sharia life insurance efficiency in Indonesia and Malaysia. The methods used in this study are descriptive and quantitative with causality design. In this study using purposive sampling technique with a total sample of 14 sharia life insurance in Indonesia and 10 sharia life insurance in Malaysia with a total of 144 observations. The data were analyzed by Data Envelopment Analysis (DEA) and tobit regression analysis methods. The results showed that the level of efficiency of sharia life insurance with the average Malaysian firm is more efficient than Indonesian companies. The level of profitability with the average is in the healthy category. The average firm size is in the category of large companies. The level of profitability and the size of the enterprise partially have a positive and significant effect on the level of efficiency. The practical implications of this study are that companies must pay attention to factors that can increase their level of efficiency by reducing operational costs and maintaining and increasing productive assets carefully.